Analysis of Legal Protection for Buyers in the Transfer of Apartment Unit Rights Prior to the Signing of the Deed of Sale and Purchase - Veronika Waruwu; Martono Anggusti; Samuel F. B. Situmorang (Al-Risalah, 2026)
The increasing demand for housing in urban areas has encouraged the development of apartment buildings as an alternative solution to meet residential needs. In practice, transactions for the sale and purchase of apartment units are often conducted before the completion of construction through a Sale and Purchase Binding Agreement (Perjanjian Pengikatan Jual Beli/PPJB), which raises legal issues related to ownership certainty and legal protection for buyers. This study aims to analyze the legal regulations governing ownership and the transfer of rights to apartment units, as well as to assess the binding force of the PPJB as an instrument of legal protection for buyers prior to the execution of the Deed of Sale and Purchase (Akta Jual Beli/AJB). This research employs a normative legal research method using a statutory approach and a conceptual approach. The analysis is conducted qualitatively on primary, secondary, and tertiary legal materials. The results indicate that legal ownership of apartment units arises juridically only after the fulfillment of legal requirements, including the completion of construction, the separation of apartment units, the execution of the Deed of Sale and Purchase before a Land Deed Official, and the issuance of a certificate in the buyer’s name. The PPJB merely creates a personal legal relationship and therefore does not transfer proprietary rights to the buyer. Consequently, in cases where the developer defaults or becomes bankrupt, buyers who only hold a PPJB are positioned as concurrent creditors and do not possess preferential rights over the bankruptcy estate. These findings demonstrate the limitations of legal protection for apartment buyers at the pre-AJB stage, highlighting the need for stronger regulatory measures to ensure legal certainty and consumer protection in apartment transactions.